Precipitation hardening in magnesium alloys - Nuttall, P.A. (1973)
Structural and kinetic aspects of precipitation in the systems Mg-Th and Mg-Nd , with various ternary additions, have been studied, using electron microscopy and electrical resistivity techniques.